WAYS TO EFFECTIVELY USE DOMESTIC INVESTMENT POTENTIAL IN THE NATIONAL ECONOMY - Namozov Olim Botirovich (Web of Journals Publishing, 2024)
This article highlights the scientific foundations for the effective use of domestic investment potential in the national economy, provides a methodology for assessing the use of domestic investment, analyzes the efficiency of capital and gives recommendations for the effective use of domestic investment.
Keywords: Investments, domestic investments, accelerator model, marginal propensity to capital, capital efficiency, efficient use of domestic investment.